Effects of femoral de-rotation on lower limb alignment using patient-specific guides with reliance on EOS scan, a retrospective study - Muhammad Taqi; Jidapa Wongcharoenwatana; Munjed Al Muderis; Mustafa Alttahir; Kevin Tetsworth; Claris Shi (Journal of Orthopaedic Surgery and Research)
Abstract The aim of this study is to evaluate the effects of midshaft femoral derotation surgery on the alignment of the lower limbs in the coronal and sagittal planes, as well as its impact on pelvic parameters in patients with significant femoral anteversion or retroversion. A retrospective review was conducted on patients who underwent femoral derotation procedures using a minimally invasive patient-specific external guide system from January 2014 to January 2022 at Macquarie University Hospital. The surgery was done using preoperative 3D modeling and patient-specific external guides. Inclusion criteria comprised patients presenting with hip, knee, or patellofemoral symptoms due to high femoral anteversion who had complete EOS scans performed preoperatively and postoperatively. The EOS imaging system was utilized for accurate assessment and comparative analysis of alignment changes following the femoral derotation. There were 22 limbs from 15 patients with an average age at operation of 30.41 ± 10.14 years (range 16.77–47.50). The average preoperative 3D EOS measurement of the femoral version in anteversion and retroversion groups were 32.84 ± 7.53° and − 22.67 ± 13.32°, respectively. The postoperative femoral version in anteversion and retroversion groups were 13.39 ± 12.90° and 3.67 ± 9.29° having p < 0.001 and p < 0.014, respectively. Paired t-test was employed to calculate statistical values. Other parameters, including Hip-knee-shaft (HKS) angle, knee angle, pelvic tilt, pelvic incidence, mechanical lateral distal femoral angle (mLDFA), and coronal plane alignment of the knee, were not statistically significant differences. This study provides evidence that femoral midshaft derotation surgery using patient-specific instrumentation (PSI) guides is an effective approach for correcting femoral anteversion and retroversion with no significant impact on coronal and sagittal lower limb alignment except femoral neck offset.